Causes of vision loss worldwide, 1990–2010: a systematic analysis - Bourne, Rupert R A; Stevens, Gretchen A; White, Richard A; Smith, Jennifer L; Flaxman, Seth R; Price, Holly; Jonas, Jost B; Keeffe, Jill; Leasher, Janet; Naidoo, Kovin; Pesudovs, Konrad; Resnikoff, Serge; et al. (The Lancet global health, 2013)
Data on causes of vision impairment and blindness are important for development of public health policies, but comprehensive analysis of change in prevalence over time is lacking. We did a systematic analysis of published and unpublished data on the causes of blindness (visual acuity in the better eye less than 3/60) and moderate and severe vision impairment ([MSVI] visual acuity in the better eye less than 6/18 but at least 3/60) from 1980 to 2012. We estimated the proportions of overall vision impairment attributable to cataract, glaucoma, macular degeneration, diabetic retinopathy, trachoma, and uncorrected refractive error in 1990–2010 by age, geographical region, and year. In 2010, 65% (95% uncertainty interval [UI] 61–68) of 32·4 million blind people and 76% (73–79) of 191 million people with MSVI worldwide had a preventable or treatable cause, compared with 68% (95% UI 65–70) of 31·8 million and 80% (78–83) of 172 million in 1990. Leading causes worldwide in 1990 and 2010 for blindness were cataract (39% and 33%, respectively), uncorrected refractive error (20% and 21%), and macular degeneration (5% and 7%), and for MSVI were uncorrected refractive error (51% and 53%), cataract (26% and 18%), and macular degeneration (2% and 3%). Causes of blindness varied substantially by region. Worldwide and in all regions more women than men were blind or had MSVI due to cataract and macular degeneration. The differences and temporal changes we found in causes of blindness and MSVI have implications for planning and resource allocation in eye care. Bill & Melinda Gates Foundation, Fight for Sight, Fred Hollows Foundation, and Brien Holden Vision Institute.